ЭКСПОЗИЦИЯ И ЕГО СЮЖЕТНЫЕ ОСОБЕННОСТИ В ЛЮБОВНЫХ ЭПОСАХ (Eurasian Journal of Philology Science and Education, 2015)
The exposition stage in Azerbaijan love eposes is an index point for succession of events and in this stage it is possible to receive about events or history not full and a certain notio